Staat und Gesellschaft in der Pandemie (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2021)
This conference volume presents lectures and discussion from the Conference of the Association of German Professors of Constitutional Law that was held in Vienna, Austria, on 9 April 2021.